Similarities in control of mini-F plasmid and chromosomal replication in Escherichia coli. - Shields, M S (1987)
In Escherichia coli, concentrations of a mini-F plasmid with two origins of replication (oriV and oriS) were 50% lower in fast-growing cells than in slow-growing cells. By contrast, a mini-F plasmid deleted for oriV maintained a uniform concentration in both fast- and slow-growing cells, and in this behavior the plasmid mimicked the control by the host of chromosomal origin (oriC) concentration.